Testing and analysis of stand-by operating modes for FRIB helium refrigeration system. Issue 1 (1st May 2022) - Kroll, D; Howard, J; Knudsen, P; Hasan, N; Ganni, V
Abstract: The main helium refrigeration system at FRIB is designed for a maximum capacity of 180 g/s (30K, 1.16 bar) cold compressor return flow, 14.0 g/s of 4.5 K liquefaction load, 4.0 kW 4.5 K refrigeration load and a 20.0 kW (35 – 55 K) thermal shield load. The helium refrigeration system operates using the Ganni Floating Pressure process and can adjust to a range of variable cryogenic load conditions without any artificial loads. It is designed considering long-term 24/7 support for the loads (cryostats and superconducting magnets) maintained at 4.5 K, without the need for a complete warm-up to room temperature. A number of maintenance, repair and outage scenarios, and the corresponding stand-by operating modes for the refrigeration system with the base-line cryogenic load have been considered, tested and analysed. This paper reports an overview of these stand-by modes and the associated analysis.